VVER-1000 reactor vessel metal state monitoring in Ukraine - V. M. Bukanov; I. M. Vyshnevskyi; M. I. Vlasenko; P. G. Lytovchenko; L. I. Chyrko (Ядерна фізика та енергетика)
On the basis of the “hot” cells of the Institute for Nuclear Research of National Academy of Sciences of Ukraine reconstitution technique of VVER reactor vessel metal surveillance specimens, and the main provisions of the reactor vessel radiation loading monitoring procedures and surveillance specimen dosimetry are described in the paper. The first results of the reconstituted irradiated surveillance specimen tests are presented, which together with the data on the radiation loading of the reactor vessel provide information for substantiation of the reactor safe operation term from the point of view of the brittle fracture resistance.